PENGEMBANGAN EVALUASI KURIKULUM BERBASIS KEBUTUHAN LOKAL STUDI KASUS DI STKIP PESISIR SELATAN: TINJAUAN LITERATUR - Revi Handayani; Fahmi Rizal; Ambiyar Ambiyar; Filma Alia Sari; Sefrinal Sefrinal (STKIP Pesisir Selatan, 2025)
This study aims to examine the concepts and practices of developing curriculum evaluation based on local needs, with a particular focus on the context of STKIP Pesisir Selatan. This review employs a literature review approach drawing on various relevant academic sources, including national and international journals, education policy reports, and institutional documents related to curriculum evaluation development. The findings indicate that curriculum evaluation based on local needs emphasizes the integration of values, potentials, and the socio-cultural characteristics of the community surrounding the campus into instructional design. At STKIP Pesisir Selatan, this approach is realized through the strengthening of curriculum evaluation that is adaptive to coastal socio-economic conditions, community empowerment, and the alignment between graduates’ competencies and regional needs. The implementation strategies involve collaboration among lecturers, students, and local stakeholders to ensure that the curriculum is not only academic in nature but also applicable in addressing contextual problems faced by the community.